Cardiomyocyte Hypocontractility and Reduced Myofibril Density in End-Stage Pediatric Cardiomyopathy - Bollen, Ilse A. E.; van der Meulen, Marijke; de Goede, Kyra; Kuster, Diederik W. D.; Dalinghaus, Michiel; van der Velden, Jolanda (Frontiers in Physiology, 2017)
Dilated cardiomyopathy amongst children (pediatric cardiomyopathy, pediatric CM) is associated with a high morbidity and mortality. Because little is known about the pathophysiology of pediatric CM, treatment is largely based on adult heart failure therapy. The reason for high morbidity and mortality is largely unknown as well as data on cellular pathomechanisms is limited. Here, we assessed cardiomyocyte contractility and protein expression to define cellular pathomechanisms in pediatric CM. Explanted heart tissue of 11 pediatric CM patients and 18 controls was studied. Contractility was measured in single membrane-permeabilized cardiomyocytes and protein expression was assessed with gel electrophoresis and western blot analysis. We observed increased Ca2+-sensitivity of myofilaments which was due to hypophosphorylation of cardiac troponin I, a feature commonly observed in adult DCM. We also found a significantly reduced maximal force generating capacity of pediatric CM cardiomyocytes, as well as a reduced passive force development over a range of sarcomere lengths. Myofibril density was reduced in pediatric CM compared to controls. Correction of maximal force and passive force for myofibril density normalized forces in pediatric CM cardiomyocytes to control values. This implies that the hypocontractility was caused by the reduction in myofibril density. Unlike in adult DCM we did not find an increase in compliant titin isoform expression in end-stage pediatric CM. The limited ability of pediatric CM patients to maintain myofibril density might have contributed to their early disease onset and severity.